Implementing a peer-support programme by group videoconferencing for isolated carers of people with dementia. (October 2019) - Banbury, Annie; Parkinson, Lynne; Gordon, Steven; Wood, Denise
Introduction: Carers support programmes are commonly delivered in person, limiting attendance opportunities for rural carers and others who have access barriers. Studies using technology typically use text-based forums rather than real-time technology such as videoconferencing (VC). Delivering home-based carers support programmes by VC may mitigate barriers for accessing support. We report implementation findings for delivering a telehealth peer-support programme for isolated carers of people with dementia. Methods: Participants were recruited through aged care providers, peak bodies and media activities. Inclusion criteria were primary dementia caregiver with Internet access and being socially or geographically isolated. The study design was a staggered randomised waitlist design. Measures included the UCLA Loneliness Scale (ULS-6) and selected scales from the e-Health Literacy Questionnaire. Recruitment activities utilised digital processes. Participants completed a six-week programme delivered by VC. Qualitative data comprised logs detailing administration and IT procedures and difficulties. Post programme, 28 participants undertook semi-structured interviews. Data were analysed using descriptive statistics and thematic analysis. Results: There were 16 groups comprising 69 participants located throughout Australia, with 87% using their own devices. Technical issues were few but included connection problems, which were compounded by low digital literacy skills. Qualitative data themes included changing perceptions in using technology, differences in communicating by VC and technical support required. Recruitment activities were time-consuming and would benefit from IT tailored for group-based work. Eight groups continued to meet on a self-organised basis. Discussion: Providing peer-support groups using telehealth may have the potential to develop self-sustaining peer networks for isolated caregivers of people with dementia.